(untitled) (Marketing Jurnali, 2025)
603 This article presents a methodology developed on the basis of a comprehensive approach to assess the quality of higher education systems using quantitative and qualitative indicators. The study introduces a system of indicators that enables an in - depth ana lysis of the activities of higher education institutions in Uzbekistan, combining international experience with national context. The proposed model covers areas such as the quality of the educational process, faculty qualifications, studentsʼ knowledge le vels, research activities, material and technical infrastructure, and the effectiveness of moral -educational work. This approach contributes to identifying internal capacities of universities, preparing globally competitive specialists, and ensuring the co ntinuous improvement of education quality.